Managemement practices related to endoparasitism in goats in Kelantan, Malaysia - Basripuzi Nurul Hayyan Hassan Basri; Sani, R.A; Hariff, O.M; Chandrawathani, P. (2012)
Endoparasitism is an important disease in small ruminants in Malaysia whose control relies largely on chemotherapeutic approach. This study was conducted to investigate the effect of selected management practices on worm burden as revealed by faecal egg count (FEC) in eight goat farms located in two districts in Kelantan. A questionnaire survey on farm practices followed by faecal sampling on 161 goats was conducted. There was no difference in the mean FEC on farms which practised grasing or no grazing. The mean FEC of goats on farms which recycled goat manure as fertiliser was found to be significantly higher(P<0.05) than those on farms which did not utilise the manure. mean FEC was significantly lower (P<0.05) in goats given local plants to treat endoparasitism compared to animals not goven the local plants. Therefore goat manure used to fertilise grasses meant for goat feed should be used with coution. Plant used by farmers as dewormers should be investigated for their anthelmintic properties.